2023
DOI: 10.1590/1519-6984.243629
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of mutated xylanase from Neocallimastix patriciarum in E. coli and application for kraft pulp biobleaching

Abstract: As an important enzyme, xylanase is widely used in the food, pulp, and textile industry. Different applications of xylanase warrant specific conditions including temperature and pH. This study aimed to carry out sodium alginate beads as carrier to immobilize previous reported mutated xylanase from Neocallimastix patriciarum which expressed in E. coli, the activity of immobilization of mutated xylanase was elevated about 4% at pH 6 and 13% at 62 °C. Moreover, the immobilized mutated xylanase retained a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Xylanase enzyme optimization was achieved at different pH and temperatures with the mutated strain Neocallimastix patriciarum. In the study, it was reported that it provides the highest activity at pH=6 and temperature at 62 o C [29].…”
Section: Findings Of Xylanase Enzyme Activity At Different Temperaturesmentioning
confidence: 99%
“…Xylanase enzyme optimization was achieved at different pH and temperatures with the mutated strain Neocallimastix patriciarum. In the study, it was reported that it provides the highest activity at pH=6 and temperature at 62 o C [29].…”
Section: Findings Of Xylanase Enzyme Activity At Different Temperaturesmentioning
confidence: 99%
“…Chen et al (2012) determined that the optimum pH range of β-glucosidase, which is defined with the number EC3.2.1.21 related to the CAZy enzyme family in the literature, is in the range of 5-6 and its molecular weight is 85.1 kDa. Mountfort et al (1989) reported that the optimum pH for its activity is 5 and the optimum temperature is 55 o C for the xylanase enzyme (EC 3.2.1.8), a member of the GH family.After the commercial use of the xylanase enzyme (Hemi-Cellulase) became widespread, Huang et al (2021) conducted immobilization studies on the gene region related to the xylanase enzyme belonging to Neocallimastix sp. Zhang et al (2019) reported the optimum in vitro working conditions of acetyl xylan esterase (CE -EC3.1.1.72) enzyme, a member of the CAZy enzyme family (Figure 3), which hydrolyzes the ester bonds of acetyl groups in the xylose parts of naturally acidified xylan substrates.…”
Section: Carbohydrate Active Enzymes System In Neocallimastix Spmentioning
confidence: 99%
“…In the present study, Xylanase was expressed and purified by Escherichia coli from a previous report ( Huang et al, 2021 ), and it was used to enzymatically hydrolyze the wheat bran to prepare feruloyl oligosaccharides. The effect of metal ions on the preparation of feruloyl oligosaccharides through hydrolyzing wheat bran by Xylanase was studied.…”
Section: Introductionmentioning
confidence: 99%